2009
DOI: 10.1016/j.jad.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Objections to suicide among depressed patients with alcohol use disorders

Abstract: Background-Understanding how alcohol misuse interacts with beliefs that protect individuals against suicide can help to enhance suicide prevention strategies. One measure of suicide nonacceptability is the Moral Objections to Suicide (MOS) subscale of the Reasons for Living Inventory (RFLI).Method-521 mood disordered patients with and without alcohol use disorders (AUD) were administered a battery of clinical measures including the Scale for Suicidal Ideation and the Reasons for Living Inventory. A multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, in patients with alcohol use disorder, lower score on the moral objections to suicide subscale of the RFLI was reported to be associated with their higher level of suicidal ideation. 46 However, the literature on this topic is scarce. Further studies are needed to investigate the protective role of religious beliefs against suicide in different psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in patients with alcohol use disorder, lower score on the moral objections to suicide subscale of the RFLI was reported to be associated with their higher level of suicidal ideation. 46 However, the literature on this topic is scarce. Further studies are needed to investigate the protective role of religious beliefs against suicide in different psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We used six items to assess daily RFL, derived from the survival and coping beliefs as well as responsibility to family subscales of the RFLI (Linehan et al, 1983). There is empirical evidence of a negative link between suicidal ideation and both survival and coping beliefs (e.g., Chang et al, 2014;Lee and Oh, 2012;Oquendo et al, 2005;Pinto et al, 1998;Richardson-Vejlgaard et al, 2009) and responsibility to family (e.g., Lee and Oh, 2012;Pinto et al, 1998;Richardson-Vejlgaard et al, 2009) subscales. Importantly for our ecological momentary assessment study design, we chose items expected to vary the most across days, while also capturing concrete positive deterrents, as opposed to items from other RFLI (Linehan et al, 1983) subscales (i.e., child-related concerns, fear of suicide, fear of social disapproval, or moral objections), which were not used in this study.…”
Section: Daily Assessmentsmentioning
confidence: 99%
“…A link between drug abuse and suicidal ideation has been well established in the literature (Borges & Loera, 2010;Richardson-Vejlgaard et al, 2009;Mino et al, 1999;Ganz & Sher, 2009). Some have suggested that all self-defeating practices (e.g., cigarette smoking, poor dietary habits) represent subtle suicidal acts, and this may represent an identifiable unconscious process from an analytic perspective, but direct correlations have only been revealed between depression and substance abuse (Ellis & Trumpower, 2008).…”
mentioning
confidence: 95%